Calculating Temperature Regime of Earth Dams in Permafrost Regions (Raschet Temleraturnogo Rezhima Zemlianykh Plorin v Raionakh Raslrostraneniia Mnogoletnei Merzloty) - Moiseev,I. S. (1974)
One of the many features of earthfill dams in the regions of persistently frozen soils is the thermal regime in the body and base of the dam. After filling of the reservoir, part of the frozen earth dam, under the effect of water's heat will thaw slowly but after the passage of a certain time depending on air temperature, temperature of water in the reservoir, material in dam body, and thickness of the permafrost layer, the thawing of the permafrost in the dam practically ceases. A steady state of temperature field sets in in which the upper part of the dam will be thawed while the central and lower sections will be frozen. In the planning of these dams, it is necessary to establish the advancement of the interface between the thawed and the frozen zone in the period after the filling of the reservoir and also the position of this boundary during a stationary state. The temperature fields within earth dams of various profiles at constant water termperatures in the reservoir and outside air can be calculated using equations presented in this paper. Draft trans. of Gidrotekhnicheskoe Stroitelstvo (USSR) v29 p281-293 1959.